Issues Associated with Burial Rites among the Idoma of North Central Nigeria - Ogbole, Friday A.; Isaac, Justus; Zingak, Deshi Lucy (Kashere Journal of Politics and International Relations, 2025)
The Idoma burial rites are deeply rooted in cultural practice that stem from the intersection of tradition, belief system, and modern influence. The study aims to unpack the dynamic of these issues of conflicts and their implications on social cohesion and individual identity. It also shed light on the diverging perspectives and customs that often clash, leading to conflict and tension within the community. This work employed a qualitative research method, utilizing an in-depth oral interview, which include focus group discussions to collate useful data from sample population of Idoma in North Central, Nigeria. The Idoma language was adopted in the interview, to ensure accurate understanding and expression of participants’ views; by analyzing the various factors at play in conflicts over burial rites among the Idoma. This work provides comprehensive understanding of the challenges and opportunities for reconciliation and peaceful coexistence in the face of divergent cultural practices.